Association Between Immigrant Status and End-of-Life Care in Ontario, Canada - Yarnell, Christopher J. (JAMA, 2017)
IMPORTANCE: People who immigrate face unique health literacy, communication, and system navigation challenges, and they may have diverse preferences that influence end-of-life care. OBJECTIVE: To examine end-of-life care provided to immigrants to Canada in the last 6 months of their life. DESIGN, SETTING, AND PARTICIPANTS: This population-based cohort study (April 1, 2004, to March 31, 2015) included 967 013 decedents in Ontario, Canada, using validated linkages between health and immigration databases to identify immigrant (since 1985) and long-standing resident cohorts. EXPOSURES: All decedents who immigrated to Canada between 1985 and 2015 were classified as recent immigrants, with subgroup analyses assessing the association of time since immigration, and region of birth, with end-of-life care. MAIN OUTCOMES AND MEASURES: Location of death and intensity of care received in the last 6 months of life. Analysis included modified Poisson regression with generalized estimating equations, adjusting for age, sex, socioeconomic position, causes of death, urban and rural residence, and preexisting comorbidities. RESULTS: Among 967 013 decedents of whom 47 514 (5%) immigrated since 1985, sex, socioeconomic status, urban (vs rural) residence, and causes of death were similar, while long-standing residents were older than immigrant decedents (median [interquartile range] age, 75 [58-84] vs 80 [68-87] years). Recent immigrant decedents were overall more likely to die in intensive care (15.6% vs 10.0%; difference, 5.6%; 95% CI, 5.2%-5.9%) after adjusting for differences in age, sex, income, geography, and cause of death (relative risk, 1.30; 95% CI, 1.27-1.32). In their last 6 months of life, recent immigrant decedents experienced more intensive care admissions (24.9% vs 19.2%; difference, 5.7%; 95% CI, 5.3%-6.1%), hospital admissions (72.1% vs 68.2%; difference, 3.9%; 95% CI, 3.5%-4.3%), mechanical ventilation (21.5% vs 13.6%; difference, 7.9%; 95% CI, 7.5%-8.3%), dialysis (5.5% vs 3.4%; difference, 2.1%; 95% CI, 1.9%-2.3%), percutaneous feeding tube placement (5.5% vs 3.0%; difference, 2.5%; 95% CI, 2.3%-2.8%), and tracheostomy (2.3% vs 1.1%; difference, 1.2%; 95% CI, 1.1%-1.4%). Relative risk of dying in intensive care for recent immigrants compared with long-standing residents varied according to recent immigrant region of birth from 0.84 (95% CI, 0.74-0.95) among those born in Northern and Western Europe to 1.96 (95% CI, 1.89-2.05) among those born in South Asia. CONCLUSIONS AND RELEVANCE: Among decedents in Ontario, Canada, recent immigrants were significantly more likely to receive aggressive care and to die in an intensive care unit compared with other residents. Further research is needed to understand the mechanisms behind this association.